The Implementation of Pancasila Student Profile Strengthening Project Entrepreneurship Theme to Enhance Student Creativity - Primadita, Sherlina; Handayani, Trisni (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
Pancasila learner profile development project (P5) aims to encourage students to contribute positively to their environment and develop strong character in accordance with Pancasila learner profile. Therefore, P5 activities have an entrepreneurial theme, where students are required to engage in P5 activities that students must achieve. By implementing P5, schools can provide opportunities for students to hone their entrepreneurial skills and introduce business concepts. Entrepreneurship is increasingly recognized as an important skill for high school students to have creativity. The purpose of this study is to describe the results of the implementation of entrepreneurship-themed P5 activities in increasing the creativity of students of Sman 91 Jakarta. This study employs descriptive qualitative with data collection through interviews, observation, and documentation with eight informants, using the results of data analysis through data reduction, display, and conclusion. The results of the analysis show that P5 activities on the theme of entrepreneurship can improve students' understanding of cooperation, innovative and creative product development, use of technology, solve problems, and improve communication and adaptation skills. So, it can be concluded that the application of the P5 theme of entrepreneurship in high school has the potential to prepare students to increase their creativity in the field of entrepreneurship and face future challenges.